The major predisposing factors to human papilloma virus (HPV) infection among patients with cancer of the cervix and their knowledge of the disease - Sibusiso SQ Mdletshe; Beverley Rasool; Lynn Lipke; Thandisizwe Redford Mavundla (AOSIS, 1997)
Objective: The purpose of this study was to identify the main predisposing factors to human papilloma virus (HPV) infection among patients with cancer of the cervix as well as establish their knowledge and awareness of the disease, so as to design educational programmes to minimise the future occurrence of the disease. Opsomming Doel: Die doel van hierdie studie was om die vernaamste predisposionele faktore tot Menslike Papilloma Virus (HPV) infeksie te identifiseer by pasiente met kanker van die serviks, insluitende hulle kennis en bewustheid van die siekte, ten einde opvoedkundige programme tot stand te bring en te ontwerp wat die hoe voorkoms van die siekte kan minimiseer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.